Nemo contra deum nisi deus ipse. Il nichilismo dell’apparenza e il re-incantamento come antidoto - Vercellone, Federico (Bollettino Filosofico, 2015)
The notion of aesthetic appearance has much to do with the history of nihilism from Plato to modern aesthetics and to Hegel. The Hegelian thesis of the “end of art” has to do with the final result of a process relegating art to the realm of appearance and condemning the rationalized world to a destiny of disenchantment. Is it possible to envisage and to elaborate a new technical “re-enchantment of the world” where theimage is becoming an ontological principle of a new idea of reality in the frame of our contemporary world dominated by images?